Reactive versus prophylactic percutaneous gastrostomy: outcomes in a cohort of advanced oropharyngeal carcinoma patients - Medeiros, Nuno; Pina, Paulo; Larangeiro, João; Oliveira, Pedro (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Dysphagia is a common complaint in patients with oropharyngeal tumors, both due to limitations of the underlying disease and the adverse effects of medical or surgical treatments. Percutaneous gastrostomy is used to prevent malnutrition, but there is currently no consensus on the best timing for its placement (prophylactic - pPEG or reactive - rPEG). The objective of this study was to analyze differences in nutritional and survival outcomes between patients who used pPEG and rPEG. Methods: Retrospective analysis of a cohort of patients with advanced-stage oropharyngeal neoplasm undergoing chemoradiotherapy between January 2013 and December 2020. PEG placement was performed before (prophylactic - pPEG) or after (reactive - rPEG) initiation of treatment. Relevant demographic and clinical variables were analyzed. Results: 49 patients received PEG during the studied period (age 57.6±8.2 years; 89.8% male). Of these, 32 (65.3%) received pPEG, while 17 (34.7%) placed rPEG. Device length of stay was significantly longer in patients with the pPEG strategy (205.5 vs 159.2 days; r=0.40; p=0.03). There was no difference in weight percentage at 3 (p=0.82) and 6 (p=0.08) months. Kaplan-Meyer analysis showed no difference in survival between the two strategies (log-rank p=0.49). Conclusions: Nutritional and survival outcomes were not statistically different between the two analyzed subgroups. PEG dependence seems to be influenced by PEG timing strategy.